Basic ship theory - Rawson, K. J. (Kenneth John), 1926-; Tupper, E. C. (Eric Charles), 1928- (Butterworth-Heinemann, 2001)
Serves as an introductory text for naval architecture students, as well as a useful reference for the more experienced designer. This volume covers the dynamics behaviour of marine vehicles, hydrodynamics, manoeuvrability and seakeeping. It concludes with some case studies of particular ship types and a discussion of maritime design.